Different, but still the same: integrative taxonomy confirms a new species of Eresus Walckenaer, 1805 (Araneae, Eresidae) from the South Caucasus - Zamani, Alireza; Seropian, Armen; Zarikian, Noushig; Bulbulashvili, Natalia; Szűts, Tamás (Pensoft Publishers, 2025)
This study represents the first step toward a systematic revision of the velvet spider genus Eresus Walckenaer, 1805 in the Caucasus. Here, Eresus transcaucasicus sp. nov. is described using an integrative approach, based on male specimens collected from the South Caucasus. The species was previously reported as E. kollari Rossi, 1846 from Armenia and as Eresus sp. from Georgia. Intraspecific variations in both coloration patterns and conductor shape, which have been rarely documented in this genus, are illustrated. The validity of previous records of E. kollari in the region is discussed.